Tubercular dactylitis with deformity ipsilateral involvement of hand and foot in an adult: a case report - Kumar, Anil; Agarwal, Shashank (International Journal of Research in Orthopaedics, 2020)
Tubercular dactylitis is a rare entity and usually involves bones of hands and feet, involvement of feet is less common. Here we report case of 18 years old female with neglected tubercular involvement of her left thumb and left great toe of foot with hallux varus deformity. Her diagnosis was delayed as she did not seek any healthcare advice for a long time and also lack of suspicion of entity. This entity which should be kept in mind when making differential diagnosis that can be treated conservatively when diagnosed early.